Copyright Historical Record Books : 1870-1977 - Library of Congress - Library Services (2021)
"The U.S. Copyright Office is governed by Title 17 of the United States Code, which requires the Register of Copyrights to maintain and provide public access to copyright records. This collection is a preview of a digitized version of the U.S. Copyright Office’s historical record books. The collection contains images of copyright applications and other records bound in books dating from 1870 to 1977. The collection offers a historically-important snapshot of the culture of the United States, primarily relating to copyrightable expression, authorship, and copyright ownership." [self-descrfiption]